Faktor-Faktor yang Memengaruhi Volume Perdagangan Sukuk Ritel SR-008 di Indonesia - Rafki, Muhammad; Wiliasih, Ranti; Irfany, Mohammad Iqbal (Penerbit Goodwood, 2022)
Purpose: To determine the factors that influence SR-008 Retail Sukuk trading volume and sukuk trading volume response to economic variable shocks. Method: VAR / VECM. The variables used consisted of price and yield of SR-008 retail sukuk, mudharabah deposit profit sharing rate, commercial bank deposit interest rates, BI Rate, inflation, and Gross Domestic Product (GDP). The period used is from March 2016 to April 2019. Result: Show that the variable interest rates on commercial bank deposits and yields have a positive effect on trade volume. While inflation, interest rates, profit sharing rates for mudharabah deposits, BI Rate and GDP have a negative effect on retail sukuk trading volume.